Populus Tremula Plants with Reduced Expression of the 4-Coumarate-CoA Ligase Gene Demonstrate Defects of the Rhizogenesis - A.Kovalitskaya, Yu.; P.Kovalenko, N.; A.Shestibratov, K. (International Journal of Engineering and Technology, 2018)
Changing expression of a single gene by introducing mutations or transformation often affects expression of other genes, which results in the modification of the plant phenotype. We have obtained aspen plants with reduced expression levels of 4CL gene (4-coumarate-CoA ligase). Change in qualitative composition and 11-23% reduced lignin content were observed in the wood of the greenhouse plants. In the study of rhizogenesis in vitro it was found that the micro shoots of transgenic plants formed a greater number of adventive roots than in the control, 30%. Studying the transgenic aspen plants grown in a greenhouse (3 months) and passed the semi-natural conditions trial (4 months) has revealed 5-10% reduction in the lignin content, alteration of the phenotype â€“ decrease in biometrical values (height and diameter of stem). Analysis of RNA from the plants grown under semi-naturalÂ  conditions indicated changed expression levels of monolignol biosynthesis genes, 4CL, CCR1 (cinnamoyl-CoA reductase), CAD6 (cinnamyl-alcohol dehydrogenase), and CCoAOMT (caffeoyl-CoA O-methyltransferase). For the lines PtXVI4CL9a and PtXIII4CL2c grown under semi-natural conditions, weight of the root system was 1.5-2 fold reduced in the transgenic plants as compared to the control. The conductive: feeding root ratio was increased. Morphology of the root system was changed.Â